Mammalian motor neurons corelease glutamate and acetylcholine at central synapses - Nishimaru, Hiroshi (National Academy of Sciences, 2005)
Motor neurons (MNs) are the principal neurons in the mammalian spinal cord whose activities cause muscles to contract. In addition to their peripheral axons, MNs have central collaterals that contact inhibitory Renshaw cells and other MNs. Since its original discovery >60 years ago, it has been a general notion that acetylcholine is the only transmitter released from MN synapses both peripherally and centrally. Here, we show, using a multidisciplinary approach, that mammalian spinal MNs, in addition to acetylcholine, corelease glutamate to excite Renshaw cells and other MNs but not to excite muscles. Our study demonstrates that glutamate can be released as a functional neurotransmitter from mammalian MNs.